EV71 infection alters the lipid composition of human rhabdomyosarcoma (RD) cells-derived extracellular vesicles - Mao, Lingxiang; Gao, Qing; Shen, Yuxuan; Bao, Chenxuan; Xiang, Huayuan; Chen, Qiaoqiao; Gao, Qianqian; Huang, Feng; He, Wenyuan; Wang, Jianjun (Frontiers in Microbiology, 2024)
Previous studies demonstrated that EV71-infected cells secrete extracellular vesicles (EVs), facilitating the transfer of viral components to recipient cells and thereby promoting virus spread. Considering lipid signaling plays a crucial role in EVs-mediated cell-to-cell communication, we compared the lipid profile of EVs secreted from uninfected and EV71-infected cells (EVs-Mock and EVs-EV71) using the human rhabdomyosarcoma (RD) cell model. These two groups of EVs were purified by using size exclusion chromatography (SEC) respectively and evaluated by transmission electron microscopy (TEM), nanoparticle tracking technology (NTA), and Western blotting (WB). In-depth lipidomic analysis of EVs identified 1705 lipid molecules belonging to 43 lipid classes. The data showed a significant increase in the lipid content of EVs after EV71 infection. Meanwhile, we deeply analyzed the changes in lipids and screened for lipid molecules with significant differences compared EVs-EV71 with EVs-Mock EVs. Altogether, we report the alterations in the lipid profile of EVs derived from RD-cells after EV71 infection, which may affect the function of the EVs in the recipient cells.